Assessment of Technological Interventions in Farm Women Empowerment (Indian Journal of Extension Education, 2021)
Women play an important role in agriculture. There is a need to empower these farm women to improve their overall wellbeing. An attempt was made to assess the impact of technological interventions in terms of participation of farm women in farming activities, change in drudgery involved, involvement in decision making and other attributes related to empowerment in North 24 Parganas district of West Bengal involving 110 farm families. The results reveal that there is significant increase in participation in all the selected farming activities in post intervention period. Majority of the farm women participated in decision making always in activities like drying (95%), weeding (70%) and storing (70%) in the post intervention period. The mean drudgery score had also decreased for all the activities, the higher decrease was observed in case of retting (1.525) followed by sowing (1.225). Among the personal attributes studied, the highest difference level in mean was attained in case of self-confidence (2.45) followed by decision making ability (2.15). The present study clearly indicate that special emphasis on women friendly technologies can make a huge change in their existing status in agriculture by improving their participation in farming activities, decision making ability and self-confidence.